Athletes` experiences of shifting from self-critical to self-compassionate approaches within high-performance sport - Frentz, D. M.; McHugh, T.-L. F.; Mosewich, A. D. (Journal of Applied Sport Psychology, 2020)
Self-compassion is associated with psychological well-being and adaptive responses; however, little is known about how athletes practically integrate self-compassion in sport. Through interpretive description, we explored how high-performance athletes shifted from self-critical to self-compassionate approaches to manage sport challenges. Eleven athletes (6 men, 5 women) participated in one-on-one interviews. Five themes were developed to encompass factors integral in participants` shifts toward self-compassion: (a) role of the coach, (b) influence of other athletes, (c) impact of important others, (d) developing balanced self-awareness, and (e) maintaining an accepting mind-set. Study findings stand to inform future intervention efforts to support adaptive athlete experiences.